PERFORMANCE OF BROILER CHICKEN FARMING IN KASHMIR VALLEY (Indian Journal of Animal Production and Management, 2014)
Two hundred day old chicks were reared on deep litter system up to 6 weeks of age to evaluate the comparative performance of broiler chicken during four different seasons viz. spring, summer, autumn and winter in Kashmir Valley of Jammu and Kashmir. The season had significant (P
Keywords: Performance; broilers; seasons; Kashmir